The Effect of Outdoor Educational Activities on Developing the Social-Emotional Learning Skills and Behaviour of Primary School Students in Fujairah - ALBAKER, KHADIJA SAEED MOHAMED (2024)
This research explored the impact of outdoor educational activities on the development of social-emotional skills and behaviours in fourth-grade primary school pupils in Fujairah. The research focused on the activities and strategies that are best suited for this specific age group. The study used a qualitative research methodology, using observation data and focus group interviews with students and teachers. This research employed a semi-experimental methodology, enabling an investigation of practical examples of outdoor educational activities. The results indicated a significant positive impact of outdoor activities on social, emotional, and behavioural development. The qualitative results indicated the enhancement of social skills, including verbal and non-verbal communication, cooperation, interaction, peer bonding, and increased teamwork abilities, in students engaged in outdoor activities. The students demonstrated a considerable improvement in emotional abilities, exhibiting empathy towards classmates in difficulty and providing mutual assistance to reduce frustration. This research revealed student behaviours that demonstrated significant improvement. The dissertation highlighted the need to use hands-on experiential outdoor activities to enhance social-emotional and behavioural development for all primary school pupils in Fujairah.